2004
DOI: 10.1590/s0100-39842004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Angiografia por ressonância magnética: aspectos técnicos de um método de estudo vascular não-invasivo

Abstract: As primeiras técnicas de angiografia por ressonância magnética (angio-RM) utilizavam seqüências sensíveis ao fluxo sanguíneo para estabelecimento do contraste vascular. Há três técnicas fundamentadas neste princípio: contraste de fase ("phase-contrast"), TOF ("time-of-flight") e as técnicas de sangue escuro ("black blood"). Estas seqüências, de aquisição demorada, são mais suscetíveis a artefatos de movimento, perda de sinal em áreas de estenoses ou turbilhonamento de fluxo, e apresentam ainda baixa sensibilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…The measurement of the blood flow by MRI is an objective technique for evaluating the portal blood flow. This method presents the advantages of providing spatial and temporal information on the blood flow in different phases of the cardiac cycle (18) and not requiring breath-hold acquisition, which could affect the hemodynamic parameters (13,14,21) . Major MRI disadvantage is related to the cost of this method, besides the lesser availability and higher complexity for evaluating the images acquired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of the blood flow by MRI is an objective technique for evaluating the portal blood flow. This method presents the advantages of providing spatial and temporal information on the blood flow in different phases of the cardiac cycle (18) and not requiring breath-hold acquisition, which could affect the hemodynamic parameters (13,14,21) . Major MRI disadvantage is related to the cost of this method, besides the lesser availability and higher complexity for evaluating the images acquired.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the mapping of the blood flow velocity by PCA MRI is a non-invasive method with good reproducibility in the quantitative measurement of the portal venous system blood flow of both healthy individuals and patients with portal hypertension (14,(17)(18)(19)(20) during normal respiration which would be considered as the most physiological situation for this study (16,17,21) . However, these studies have been developed with obsolete equipment in low magnetic field and with outdated techniques, besides not evaluating the MRI reproducibility (interobserver agreement).…”
Section: Introductionmentioning
confidence: 99%
“…Em geral os contrastes comerciais exibem um gosto mais amargo, sua consistência é mais espessa e a coloração não é muito agradável. Além disso, após a ingestão os pacientes podem apresentar reações de náuseas e vômitos (FILHO et al, 2002;CALDANA et al, 2004;SANCHEZ et al, 2009 e algumas mais raras como urticária e pruridos. Desta forma, um contraste natural (suco de fruta ou polpa de fruta) que possa substituir o comercial em exames é uma alternativa saudável, econômica, viável, mais palatável, menos tóxica e que visa manter a qualidade das imagens e a satisfação do paciente, independentemente da idade do mesmo (ALMIRO et al, 2016).…”
Section: Fonte:ursini 1997 (Adaptado)unclassified
“…Esta técnica tem sido cada vez mais utilizada como método de estudo vascular, merecendo destaque na avaliação de anomalias anatômicas, estenoses, oclusões e complicações vasculares póscirúrgicas, principalmente no caso de transplante de órgãos. Sua principal vantagem é ser um método não invasivo, que não utiliza radiações ionizantes e que dispensa o uso de contraste iodado, potencialmente alergênico e nefrotóxico, além da rapidez e facilidade de execução (Caldana et al, 2004).…”
Section: Conclusãounclassified